The role of hyperbaric oxygen therapy and antioxidant administration in treatment of idiopathic male infertility - D. G. Korenkov; S. N. Kalinina; V. N. Fesenko; A. L. Pavlov (Андрология и генитальная хирургия, 2018)
Introduction. In clinical andrology practice, the cause of infertility in 40–70 % cases is idiopathic male infertility. The treatment involves empirical therapy based on the knowledge of  spermatogenesis. In recent years, dietary supplements are used as  the first line therapy of male infertility. Among these multicomponent dietary supplements are combination supplement for increasing male fertility Speroton and antioxidant complex Sinergin (Acvion, Russia).The study objective is to optimize the results of hyperbaric oxygen therapy (HBOT) in combination treatment of patients with idiopathic abnormalities in semen analysis.Materials and methods. The study included 155 males aged 20–45 years. Among them, 120 males were diagnosed with idiopathic infertility, 35 were practically healthy (control group). Patients with  infertility (n = 120) were divided into 3 groups, 40 patients each. In  all 3 groups, patients received HBOT in combination with Speroton  and/or Sinergin: the 1st group (n = 40) received Speroton (1  sachet/day); the 2 nd group (n = 40) received HBOT and Sinergin (2 capsules/day); patients in the 3 rd group received combination of  HBOT + Speroton (one sachet/day) + Sinergin (2 capsules/day). Patients in the 3 groups continued to receive the supplements 3 months after the completion of HBOT. The HBOT course consisted of  10 60-minute daily sessions. In patients of the 4 groups, including  the control group, the levels of oxidative stress products and  endogenous antioxidants activity in plasma and ejaculate were  evaluated, as well as the main semen characteristics. Results. The administered therapies normalized thiol-disulfide metabolism in plasma and semen, antioxidant protection, and the main semen characteristics. In patients of the 1st group (HBOT +  Speroton), sperm count in the ejaculate increased 3-fold compared  to the baseline (before treatment), motile sperm forms increased  2.4-fold, the number of degenerated sperm cells decreased 1.3-fold.  In the 2 nd group (HBOT + Sinergin), sperm count in the ejaculate  increased 2.2-fold in the course of treatment, motile sperm count  increased 2.7-fold, the number of degenerated sperm cells  decreased 1.4-fold. In the 3 rd group (HBOT + Speroton + Sinergin), sperm count in the ejaculate increased 4.7-fold, motile sperm count – 5.3-fold, the number of degenerated sperm cells decreased 1.8- fold.Conclusion. Combined administration of Speroton and Sinergin in combination with HBOT has shown high effectiveness in correction of the main ejaculate characteristics and can be recommended as a therapy for various forms of asthenozoospermia.